STRATEGI KELUARGA DALAM MENGHADAPI KENAIKAN HARGA - Armaini Rambe (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACT The increase inprices of variousessential commoditieshave an impact onthe decliningpurchasing power ofthe community. Felt the most impactison families.Familiesare required tomeet the needs oflivingwithlimitations. Optimalresource managementfamilythatcan maximizeall the problemsfaced byfamiliesin the face ofprice increase.Strategiesthat familiesin the face ofprice risecrisisisthrough changes inthe frequencyandqualityof foodandnon-foodexpenditures, changes inthe quality offood and non foodproducts, changes in the qualityof foodandnon-foodconsumption.The whole family, including husband, wife, children andother relativesinvolvedin optimizingthe resourcesowned bythe familythata family destinationis reachedandstillsurvive. Kata Kunci : Keluarga, kenaikkan harga.